Resistência antimicrobiana e prevalência de sorovares de salmonella spp. isolados de fezes e linfonodos de suinos - Guerra Filho, João Bosco Pereira [UNESP] (2014)
The objective of this study was to evaluate the prevalence of Salmonella spp. and their antibiotic resistance profiles in swine slaughtered in abattoirs under federal inspection located in the state of São Paulo. For both types of samples, such as feces and mediastinal, mesenteric and submandibular lymph nodes, 50 samples of each type being possible to evaluate the relevance of the type of material analyzed in relation to the actual status of the animal against the contamination by the pathogen were used. Based on positive samples, serotyping of the strains and antibiotic resistance test was performed. The prevalence of the pathogen was 10% of total samples (20/200) wich the highest positivity found in the submandibular lymph nodes with 20% positive (10/50) and mesenteric with 18% (9/50) and lower found in the feces with 2% positive (1/50) and mediastinal lymph nodes with no positive sample. The predominant serotypes were S.Typhimurium with 55% of the samples (11/20) followed by S. enterica subspecies enterica 4,5,12: i: -, 35% (7/20) and the serotypes S. Brandenburg and S. derby 5% (1/20) each. All isolates were resistant at least one of the antimicrobials tested, among them 90% (18/20) showed resistance to at least four drugs simultaneously and 15% (3/20) were classified as multi drug resistant. The highest rates were found for Ciprofloxacin and Tetracycline resistance with 90% (18/20) each, followed by Nalidixic Acid with 80% (16/20), Sulfonamides 75% (15/20), Chloramphenicol and Streptomycin with 70% (14/20) each, Trimethoprim-Sulfamethoxazole 65% (13/20), Ampicillin 25% (5/20), Cefotaxime 10% (2/10) and Ceftriaxone and Gentaminicine with 5% (1/20) each. Resistant to Ciprofloxacin samples were tested for the presence of ESBL enzyme, 100% of them considered negative